Boron Tetrafluoride Anion Bonding Dual Active Species Within a Large–Pore Mesoporous Silica for Two–Step Successive Organic Transformaion to Prepare Optically Pure Amino Alcohols - Li, Liang; Yang, Dongfeng; Zhao, Zhongrui; Song, Yongkang; Zhao, Lei; Liu, Rui; Liu, Guohua (Frontiers in Chemistry, 2018)
Development of a simple and easy handing process for preparation of multifunctional heterogenous catalysts and exploration of their applications in sequential organic transformation are of great significance in heterogeneous asymmetric catalysis. Herein, through the utilization of a BF4− anion–bonding strategy, we anchor conveniently both organic bases and chiral ruthenium complex into the nanopores of Me-FDU–12, fabricating a Lewis base/Ru bifunctional heterogeneous catalyst. As we envisaged, cyclic amine as a Lewis base promotes an intermolecular aza–Michael addition between enones and arylamines, affording γ–secondary amino ketones featuring with aryl motif, whereas ruthenium/diamine species as catalytic promoter boosts an asymmetric transfer hydrogenation of γ–secondary amino ketones to γ–secondary amino alcohols. As expected, both enhance synergistically the aza–Michael addition/asymmetric transfer hydrogenation one–pot enantioselective organic transformation, producing chiral γ–secondary amino alcohols with up to 98% enantioselectivity. Unique features, such as operationally simple one–step synthesis of heterogeneous catalyst, homo–like catalytic environment as well as green sustainable process make this heterogeneous catalyst an attracting in a practical preparation of optically pure pharmaceutical intermediates of antidepressants.